The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1007/bf02464778
|View full text |Cite
|
Sign up to set email alerts
|

Physics 1800–1900: A quantitative outline

Abstract: The authors utilize the index of the Catalogue of Scientific Papers of the Royal Society of London dealing with the physics journal literature of the 19th century. Graphs of the publication activity of the entire 19th-century physics and of about 50 of its most important subareas are displayed; both the number of active contributors in each area, the number of papers and its share of publications of the entire 19th century physics are exhibited. Typical scientometric regularities such as "Lotka's law" (with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Seventy‐five years ago, Lotka (1926) discovered that the distribution of publications across authors in chemistry was described by the following relationship, where f ( n ) is the fraction of authors having n publications and A is a constant. Since then, numerous other studies have found the same relationship for many fields (Narin & Breitzman, 1995; Pao, 1986; Shockley, 1957; Wagner‐Dobler & Berg, 1999). The findings are so ubiquitous that it has become known as Lotka's Law.…”
Section: Introductionmentioning
confidence: 62%
“…Seventy‐five years ago, Lotka (1926) discovered that the distribution of publications across authors in chemistry was described by the following relationship, where f ( n ) is the fraction of authors having n publications and A is a constant. Since then, numerous other studies have found the same relationship for many fields (Narin & Breitzman, 1995; Pao, 1986; Shockley, 1957; Wagner‐Dobler & Berg, 1999). The findings are so ubiquitous that it has become known as Lotka's Law.…”
Section: Introductionmentioning
confidence: 62%
“…As can be seen, larger values of a/b require larger critical values for N. Also, the model predicts that, since the natural logarithm of N plays a role in the value of Dz, disproportionate increases of N are required to maintain the same levels of scientific growth once N gets substantially large. Quantitative studies that link the size of the scientific community and scientific discovery in diverse disciplines are in line with this prediction, including genetics (Glass 1979) and physics (Wägner-Dobler and Berg 1999). In this latter study, one can see, for example, a concurrence between a steep increase in the number of authors working on electricity and magnetism in the mid nineteenth century with important discoveries in that field, such as Maxwell's unification of electricity, magnetism and light into a single theory of the electromagnetic field in the 1860s (Wägner-Dobler and Berg 1999, p. 256).…”
Section: The Cultural Transmission Of Scientific Knowledge: a Modelmentioning
confidence: 87%
“…In this study, the bibliometric method was employed to get an overview of JMS over the last 35 years. Bibliometric analysis, based on statistical data about publications, citations, and other related indicators, has been widely used to reveal objective performance and development of scientific journals; for example, the American Journal of Roentgenology (Elster and Chen, 1994;Chen et al, 2003), Physics (Wagner-Dobler and Berg, 1999), the American Journal of Veterinary…”
Section: Introductionmentioning
confidence: 99%